NOP132 is required for proper nucleolus localization of DEAD-box RNA helicase DDX47 - Sekiguchi, Takeshi (Oxford University Press, 2006)
Previously, we described a novel nucleolar protein, NOP132, which interacts with the small GTP binding protein RRAG A. To elucidate the function of NOP132 in the nucleolus, we identified proteins that interact with NOP132 using mass spectrometric methods. NOP132 associated mainly with proteins involved in ribosome biogenesis and RNA metabolism, including the DEAD-box RNA helicase protein, DDX47, whose yeast homolog is Rrp3, which has roles in pre-rRNA processing. Immunoprecipitation of FLAG-tagged DDX47 co-precipitated rRNA precursors, as well as a number of proteins that are probably involved in ribosome biogenesis, implying that DDX47 plays a role in pre-rRNA processing. Introduction of NOP132 small interfering RNAs induced a ring-like localization of DDX47 in the nucleolus, suggesting that NOP132 is required for the appropriate localization of DDX47 within the nucleolus. We propose that NOP132 functions in the recruitment of pre-rRNA processing proteins, including DDX47, to the region where rRNA is transcribed within the nucleolus.